A mutation in a C2H2-type zinc finger transcription factor contributed to the transition toward self-pollination in cultivated tomato. Issue 10 (2nd August 2021) - Shang, Lele; Song, Jianwen; Yu, Huiyang; Wang, Xin; Yu, Chuying; Wang, Ying; Li, Fangman; Lu, Yongen; Wang, Taotao; Ouyang, Bo; Zhang, Junhong; Larkin, Robert M; et al.
Abstract: The degree of stigma exsertion has a major influence on self-pollination efficiency in tomato, and its improvement is essential for raising productivity and for fixing advantageous traits in cultivated tomato. To study the evolution of stigma exsertion degree in tomato, we searched for genes associated with this trait and other aspects of flower morphology, including the lengths of anthers, styles, and ovaries. We performed a genome-wide association on 277 tomato accessions and discovered a novel stigma exsertion gene ( SE3.1 ). We reannotated the structure of the gene, which encodes a C2 H2 -type zinc finger transcription factor. A mutation of the lead single nucleotide polymorphism creates a premature termination codon in SE3.1 and an inserted stigma in cultivated tomatoes. SE3.1 is essential for the conversion of flush stigmas to inserted stigmas. This conversion has a major impact on the rate of self-fertilization. Intriguingly, we found that both SE3.1 and Style2.1 contribute to the transition from stigma exsertion to insertion during the domestication and improvement of tomato. Style2.1 controls the first step of exserted stigmas to flush stigmas, and SE3.1 controls the second step of flush stigmas to inserted stigmas. We provide molecular details for the two-step process that controls the transition from stigma exsertion to insertion, which is of great agronomic importance in tomato. Abstract : A mutation in SE3.1 leads to the development of inserted stigmas in cultivated tomatoes, which together with Style2.1 contributed to the transition from exserted to inserted stigmas.